2021
DOI: 10.1039/d0re00431f
|View full text |Cite
|
Sign up to set email alerts
|

Sorption enhanced dimethyl ether synthesis under industrially relevant conditions: experimental validation of pressure swing regeneration

Abstract: High single-pass production of dimethyl ether from CO2-rich feedstock is demonstrated by pressure swing regeneration, allowing enormous increase in productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…39,43 Emerging production routes focus on the coupling of reaction and separation. Hereby, sorption-based [44][45][46] and membrane-based 47,48 methods have been investigated. A particular promising approach in the scope of CO 2 -utilisation is the DME synthesis via reactive distillation.…”
Section: State-of-the-art Of Dme Synthesis and Dme Reformingmentioning
confidence: 99%
“…39,43 Emerging production routes focus on the coupling of reaction and separation. Hereby, sorption-based [44][45][46] and membrane-based 47,48 methods have been investigated. A particular promising approach in the scope of CO 2 -utilisation is the DME synthesis via reactive distillation.…”
Section: State-of-the-art Of Dme Synthesis and Dme Reformingmentioning
confidence: 99%
“…11 SER: green. 4,15 Thermodynamic equilibrium at 250 C and 25-50 bar: black. Theoretical maximum: red.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…11 In parallel, sorption enhanced technology for the production of DME has been developed and scaled up in recent years. 4,[12][13][14][15][16][17][18] Interestingly, the most promising materials for high temperature steam adsorption are again LTAtype zeolites. LTA zeolites, and specically 3A, are highly selective for water due to size exclusion by the limited pore size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…De Falco et al reported that a DME yield of 75% can be obtained with a membrane reactor configuration for an optimized case with an operating pressure of 70 bar. Comparable performances are obtained at 30 bar using the reactive steam adsorption. In this process configuration, also known as sorption enhanced DME synthesis (SEDMES), the two catalysts (methanol synthesis and dehydration) used for the direct DME synthesis are mixed with a selective water adsorbent such as LTA zeolite 3A or 4A. The resulting lumped stoichiometries, considering CO and CO 2 as carbon sources, and the corresponding reaction enthalpies evaluated assuming a water adsorption enthalpy of Δ H ads = −46.0 kJ/mol, are reported in eq and , respectively. SEDMES is an intrinsically cyclic process in which the adsorption/reaction step is followed by a regeneration phase, required to remove the water stored in the adsorbent material. , …”
Section: Introductionmentioning
confidence: 99%